The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00438-003-0876-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structure and inheritance of a linear plasmid from the obligate biotrophic fungus Blumeria graminis f. sp. hordei

Abstract: A linear plasmid is widespread among isolates of the obligate biotrophic fungus Blumeria graminis f.sp. hordei (synonym Erysiphe graminis) (Bgh), the organism that causes the disease powdery mildew on barley. We cloned and sequenced the entire plasmid of 7965 bp. The plasmid contains two identical terminal inverted repeats (TIR) of 610 bp. Two ORFs are present on opposite strands, one encoding a phage-type DNA polymerase and the other a phage-type RNA polymerase. Two large transcripts of approximately 4.2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Relationships between mitochondrial plasmids from different species have been estimated using DPO and RPO nucleotide and amino acid sequences. The transmission of mitochondrial plasmids during reproduction in fungi has been the subject of many studies (Giese et al, 2003), including investigations of introgression in Neurospora (Bok et al, 1999) and asexual transmission in Cryphonectria parasitica (Murrill) ME Barr (Baidyaroy et al, 2000). Other research has shown that despite the existence of somatic incompatibility barriers, plasmid transmission has also occurred by anastomosis (Giese et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between mitochondrial plasmids from different species have been estimated using DPO and RPO nucleotide and amino acid sequences. The transmission of mitochondrial plasmids during reproduction in fungi has been the subject of many studies (Giese et al, 2003), including investigations of introgression in Neurospora (Bok et al, 1999) and asexual transmission in Cryphonectria parasitica (Murrill) ME Barr (Baidyaroy et al, 2000). Other research has shown that despite the existence of somatic incompatibility barriers, plasmid transmission has also occurred by anastomosis (Giese et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial plasmids are widely distributed in filamentous fungi and exhibit some common features, such as the presence of terminal inverted repeats (TIRs) and genes encoding DNA and RNA polymerases (DPO and RPO, respectively;Kempken et al, 1992;Kempken, 1994;Cahan and Kennel, 2005). Such plasmids are found in various Ascomycota and Basidiomycota species, including several saprophytes and plant pathogens (Giese et al, 2003), particularly in the genus Neurospora (Xu et al, 1999). They are often transmitted in the same manner as mitochondria and mitochondrial DNA, and during sexual reproduction, maternal plasmids are inherited by most or all of the resulting progeny.…”
Section: Introductionmentioning
confidence: 99%